Population Pharmacokinetics of Amitriptyline After Intrathecal, Epidural, and Intravenous Administration in Sheep. Issue 6 (November 2015) - Ratajczak-Enselme, Maja; Grégoire, Nicolas; Estebe, Jean-Pierre; Dollo, Gilles; Chevanne, F.; Bec, David; Ecoffey, Claude; Couet, William; Le Corre, Pascal
Abstract : Background: Amitriptyline (AMI) is a lipophilic, tricyclic antidepressant with analgesic properties that could potentially be used for epidural (EPI) analgesia. However, no pharmacokinetic data are available for AMI in spinal spaces. The objective of this study was to evaluate the spinal disposition and intrathecal (IT) bioavailability of AMI after IT and EPI administration. Methods: Six Lacaune ewes received 3 consecutive administrations of AMI. They initially received 10 mg of AMI administered intravenously, then 5 mg of AMI administered intrathecally, and 50 mg of AMI injected into the EPI space. Consecutive administrations were separated by intervals of 2 hours. A simultaneous microdialysis technique was used to determine the EPI and IT concentrations of AMI. Population analysis with S-ADAPT software was used to evaluate the pharmacokinetic parameters. Results: Following intravenous administration, the clearance and central compartment ( V c ) in plasma were 1.32 L/min and 147 L, respectively. Concentration-time profiles for the IT and EPI compartments were highly variable after transmeningeal diffusion. The IT V c after IT administration and the EPI V c after EPI administration were 2.4 and 48.9 mL, respectively. Less AMI transferred from the EPI to the IT space than from the IT to the EPI compartment, with bioavailabilities of 1.3% and 55%, respectively. Conclusions: Simultaneous population analysis for AMI demonstrated differences in EPI and IT pharmacokinetics following the EPI and IT administration of this drug. The IT bioavailability of AMI after EPI administration is relatively low. Abstract : Supplemental digital content is available in the text.